Contribution of tidal power generation system for damping inter-area oscillation - Mehri,S (2017)
The growing need for the clean and renewable energy has led to the fast development of grid-connected tidal stream power generation systems all over the world. These large scale tidal stream power generation systems are going to be connected to power systems and one of the important subjects that should be investigated is its impacts on power system stability. Hence, this paper investigates the possibility of tidal stream power generation system on damping inter-area oscillations, as a new contribution to earlier studies. As tidal farms are mostly installed far from conventional power plants, local signals do not include good quality to alleviate inter-area oscillations. To overcome the problem, a novel damping controller is developed by employing wide-area measurement system and added to base controllers of doubly-fed induction generator through tidal stream power generation system. The proposed wide area damping controller includes efficient means to compensate for the incompatible performances of wide area measurement based delayed signals. Robustness of the designed damping controller has been demonstrated by facing the study system with faults leading to enough shifts in power system operating point, and tidal farm generation.